2021
DOI: 10.3390/diagnostics11122288
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Deep Ensemble Learning Method for Dynamic Evolving Diagnostic Task Scenarios

Abstract: Increasingly, machine learning methods have been applied to aid in diagnosis with good results. However, some complex models can confuse physicians because they are difficult to understand, while data differences across diagnostic tasks and institutions can cause model performance fluctuations. To address this challenge, we combined the Deep Ensemble Model (DEM) and tree-structured Parzen Estimator (TPE) and proposed an adaptive deep ensemble learning method (TPE-DEM) for dynamic evolving diagnostic task scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In the study described in this paper, the ensemble learning approach had higher AUC and CV AUC scores, but the model without the ensemble approach had higher testing and average CV accuracy. Although studies that focused on the prediction of the risk for T2D reported improved results with the inclusion of ensemble learning methods, our results suggest that ensemble learning will not always yield higher metric scores [ 39 ].…”
Section: Discussionmentioning
confidence: 85%
“…In the study described in this paper, the ensemble learning approach had higher AUC and CV AUC scores, but the model without the ensemble approach had higher testing and average CV accuracy. Although studies that focused on the prediction of the risk for T2D reported improved results with the inclusion of ensemble learning methods, our results suggest that ensemble learning will not always yield higher metric scores [ 39 ].…”
Section: Discussionmentioning
confidence: 85%
“…The proposed model determines the optimal number of layers and basic learners based on the distribution of data and characteristics of the diagnostic task, resulting in improved performance compared to other baseline models. This approach offers a novel solution for developing straightforward and interpretable machine learning models in computer-aided diagnosis tasks that involve diverse datasets and feature sets [10] augmentation, stacking, and bagging, on performance. The pipeline was tested on four medical imaging datasets and demonstrated that stacking achieved the highest performance boost, with up to a 13% rise in F1-score.…”
Section: Literature Reviewmentioning
confidence: 99%